2017
DOI: 10.1038/s41598-017-14873-0
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Thiazolidinediones on In-Stent Restenosis and Target Lesion Revascularization after PCI: A Meta-Analysis of Randomized Controlled Trials

Abstract: In-stent restenosis (ISR) remains the leading problem encountered after percutaneous coronary intervention (PCI). Thiazolidinediones (TZDs) has been shown to be associated with reduced ISR and target lesion revascularization (TLR); however, the results are inconsistent, especially between rosiglitazone and pioglitazone. In this study, fourteen RCTs with a total of 1350 patients were finally included through a systematical literature search of Embase, Pubmed, the Cochrane Library, and ClinicalTrials.gov from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“… 130 , 132 TZDs exert antiproliferative, antiplatelet, and anti-inflammatory effects and promote VSMC differentiation ( Fig 5 ). PPAR-γ agonists decrease intimal hyperplasia after PCI, 133 , 134 and vascular PPAR-γ expression was strongly repressed after arterial stenting in minipigs. Systemic rosiglitazone treatment rescued both PPAR-γ and contractile protein expression after stenting and decreased inflammation.…”
Section: Potential New Avenues For Therapeutic Modulation Of Smc Phenotype In Intimal Hyperplasiamentioning
confidence: 98%
“… 130 , 132 TZDs exert antiproliferative, antiplatelet, and anti-inflammatory effects and promote VSMC differentiation ( Fig 5 ). PPAR-γ agonists decrease intimal hyperplasia after PCI, 133 , 134 and vascular PPAR-γ expression was strongly repressed after arterial stenting in minipigs. Systemic rosiglitazone treatment rescued both PPAR-γ and contractile protein expression after stenting and decreased inflammation.…”
Section: Potential New Avenues For Therapeutic Modulation Of Smc Phenotype In Intimal Hyperplasiamentioning
confidence: 98%
“…Some pioneering studies on the preventive medication to ISR showed that thiazolidinedione (TZD) treatment for 6 to 18 months significantly reduced the incidence of ISR, target lesion revascularization, and major adverse cardiovascular events in patients after PCI, and Pioglitazone treatment seems to have more beneficial effects than Rosiglitazone. 36 Nevertheless, few studies have shown the efficacy and safety of herbal medicines in preventing ISR incidence. Our data in another study found that RSD combined with remote ischemic preconditioning did not significantly affect angina attack and prognosis of CHD, but decreased the frequency of emergency medications in CHD patients, indicating a therapeutic effect of RSD in CHD.…”
Section: Discussionmentioning
confidence: 99%
“…In our study compliance with double antiplatelet therapy was good, with no statistically significant differences between patients with or without stent angiographic restenosis. Information on the possible protective effect of anti-diabetic medication on stent restenosis is inconsistent and inconclusive [11,[29][30][31][32]. Several studies have suggested that some oral antidiabetics, such as thiazolidinediones, lower the risk of stent restenosis and major post-procedural cardiac events [11,29].…”
Section: Roc Curve For the Logistic Regression Modelmentioning
confidence: 99%
“…Information on the possible protective effect of anti-diabetic medication on stent restenosis is inconsistent and inconclusive [11,[29][30][31][32]. Several studies have suggested that some oral antidiabetics, such as thiazolidinediones, lower the risk of stent restenosis and major post-procedural cardiac events [11,29]. On the other hand, although preclinical studies have indicated that insulin administration reduces intimal hyperplasia, the incidence of in-stent restenosis does not appear to be influenced when comparing insulin therapy with usual care with oral hypoglycaemic agents [30].…”
Section: Roc Curve For the Logistic Regression Modelmentioning
confidence: 99%